Brazil’s achievements in improving stunting prevalence and breastfeeding practices: Ingredients of success - Requejo, Jennifer (International Food Policy Research Institute, 2014)
Maternal and child undernutrition remains an important public health problem. The objective of this research is to examine the relative influence of maternal prepregnancy weight (PPW) and gestational weight gain (GWG) on birth size for 971 singleton live births born to women who participated in a pre‐conceptional micronutrient supplementation trial in Vietnam. Adjusted generalized regression models were used to examine associations with birth weight, BW (mean + SD: 3054 + 400 g); small for gestational age, SGA (22%); and low birth weight, LBW (5%). A 1 SD increase in PPW was associated with a 226 g (95%CI: 220‐231) increase in BW. Similar and independent effects were observed for BW (226 g; 95%CI: 219 – 233) per SD increase in GWG. The relative impact of a 1 SD increase in PPW and GWG were similar for length (0.17 and 0.14 cm), head circumference (0.13 and 0.15 cm) and MUAC (0.15 and 0.14 cm) at birth, respectively. A 1 kg increase in PPW and GWG was also associated with a 9.4% and 9.5% reduction in the risk of delivering a SGA infant and 12% and 15% for LBW, respectively. Women with pre‐pregnancy BMI < 17 kg/m2 (moderate‐severe thinness) or in the lower tertile of GWG had 2.4 – 2.6 times the risk for SGA and 3.9 – 4.6 times the risk for LBW. These findings indicate that programs aimed at improving birth outcomes will have the greatest impact if they address maternal nutrition both before and during pregnancy.Grant Funding Source: Supported by the Micronutrient Initiative & the Mathile Institute for Advancement of Human Nutrition